The first tidal analysis based on the CG-5 Autograv gravity measurements at Modra station - MIKOLAJ, Michal; HÁBEL, Branislav (Contributions to Geophysics and Geodesy, 2013)
We present the tidal parameters estimated for the absolute gravity site in Modra (Slovakia). This is the first tidal analysis based on gravity measurements for this location. Relative gravity variations observed by Scintrex CG-5 Autograv gravimeter were used for the tidal analysis. We observed large and non-linear instrumental drift which cannot be effectively eliminated by polynomial approximation. Drift was eliminated by a filtering. New set of tidal parameters was estimated and analyzed with the focus on diurnal and semi-diurnal tidal waves. Time and frequency domain comparison between new parameters and those obtained from the superconducting gravimeter located in Vienna was performed. A maximum amplitude factor difference of 0.2% was found between main tidal waves corrected for ocean tides and non-hydrostatic body tide model. New estimated tidal parameters can serve for the correction of local relative gravity measurements.